2005
DOI: 10.1074/jbc.m411485200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Genetic Studies Imply Akt-mediated Signaling Promotes Protein Kinase CβII Alternative Splicing via Phosphorylation of Serine/Arginine-rich Splicing Factor SRp40

Abstract: Insulin regulates splicing of pre-mRNA for protein kinase C␤II (PKC␤II) 1 by enhanced exon inclusion in rat skeletal muscle myotubes (L6) (1, 2). Alternative splicing of nuclear pre-mRNA allows for the formation of multiple RNA isoforms from a single primary RNA transcript. It is a widespread mechanism controlling gene expression in higher eukaryotes (3), and an estimated 30,000 human genes generate over 100,000 protein isoforms with distinct functions by alternative splicing (4, 5). Alternative splicing can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
101
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 60 publications
1
101
0
Order By: Relevance
“…Recent works have provided in vitro and in vivo evidence showing that PI3K/AKT pathway regulates specific alternative splicing events through phosphorylation of selective SR proteins (Blaustein et al, 2005;Patel et al, 2005). Here, we provide the first observation that couples a functionally critical alternative splicing event to a signaling cascade that has an essential role in Epo-induced erythropoiesis.…”
Section: Discussionmentioning
confidence: 71%
“…Recent works have provided in vitro and in vivo evidence showing that PI3K/AKT pathway regulates specific alternative splicing events through phosphorylation of selective SR proteins (Blaustein et al, 2005;Patel et al, 2005). Here, we provide the first observation that couples a functionally critical alternative splicing event to a signaling cascade that has an essential role in Epo-induced erythropoiesis.…”
Section: Discussionmentioning
confidence: 71%
“…In mammalian cells, insulin regulates alternative splicing of PKC␤II (45,46). The effect of insulin upon alternative splicing of PKC␤II is coincident with an increase in the phosphorylation of SRSF5 (11). In hepatocytes in culture, insulin increases G6PD mRNA and increases SR protein phosphorylation, including phosphorylation of SRSF3 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To date, multiple kinases, including SR protein kinase 1 (SRPK1) (36), SRPK2 (37), Cdc-like kinase (Clk/Sty) (38), DNA topoisomerase I (39), cAMP-dependent protein kinase (PKA), and AKT (40,41), have been shown to phosphorylate the RS domain of SF2/ASF. We recently found that Dyrk1A phosphorylates SF2/ASF, SC35, and 9G8 and regulates both subcellular localization and activity (13,14,19).…”
Section: Discussionmentioning
confidence: 99%